Estimation of outcrossing rate in a breeding population of Eucalyptus urophylla with dominant RAPD and AFLP markers - Gaiotto, F. A.; Bramucci, M.; Grattapaglia, D. (Springer, 1997)
Eucalyptus breeding is typically conducted by selection in open-pollinated progenies. As mating is controlled only on the female side of the cross, knowledge of outcrossing versus selling rates is essential for maintaining adequate levels of genetic variability for continuous gains. Outcrossing rate in an open-pollinated breeding population of Eucalyptus urophylla was estimated by two PCR-based dominant marker technologies, RAPD and AFLP, using 11 open-pollinated progeny arrays of 24 individuals. Estimated outcrossing rates indicate predominant outcrossing and suggest maintenance of adequate genetic variability within families. The multilcous outcrossing rate (t(m)) estimated from RAPD markers (0.93 +/- 0.027), although in the same range, was higher (alpha > 0.01) than the estimate based on AFLP (0.89 +/- 0.033). Both estimates were of similar magnitude to those estimated for natural populations using isozymes. The estimated Wright's fixation index was lower than expected based on t, possibly resulting from selection against selfed seedlings when sampling plants for the study. An empirical analysis suggests that 18 is the minimum number of dominant marker loci necessary to achieve robust estimates of t,. This study demonstrates the usefulness of dominant markers, both RAPD and AFLP, for estimating the outcrossing rate in breeding and natural populations of forest trees. We anticipate an increasing use of such PCR-based technologies in mating-system studies, in view of their high throughput and universality of the reagents, particularly for species where isozyme systems have not yet been optimized.
Keywords: mating system; AFLP; RAPD; Eucalyptus